Factors influencing rate of gain, quantity of feed consumed and carcass grade, 1948-49. - Bell, F.W.; Mackintosh, D.L.; Pickett, A.G. (Kansas Agricultural Experiment Station, 2012)
This report is on two lots of heifer calves now on test in the study of the characteristics of feeder calves which are associated with differences in: 1. Rate of gain 2. Kind and amount of feeds required to produce gains. 3. Value of the carcass. The two lots were selected from 100 heifer calves purchased in November 1948 for feeding tests. These calves graded good to choice as feeders. There was more difference in the condition of the calves when received than there was in those used in the similar trial of 1947-48. This fact may account in part for the differences in results to date as compared with last year's results. The two lots in this trial were sorted by the same method used last year, on the basis of differences in body capacity, chest room, fleshing, form and general appearance. The ten calves in lot 1 are those which were somewhat deficient in one or more of the above characteristics as compared to those in lot 2. All calves were graded individually by using a standard feeder cattle chart.
Keywords: Beef; Rate of gain; Carcass grade; Feed consumption